2016
DOI: 10.1038/srep38179
|View full text |Cite
|
Sign up to set email alerts
|

Dysbiosis by neutralizing commensal mediated inhibition of pathobionts

Abstract: Dysbiosis in the periodontal microbiota is associated with the development of periodontal diseases. Little is known about the initiation of dysbiosis. It was hypothesized that some commensal bacteria suppress the outgrowth of pathobionts by H2O2 production. However, serum and blood components released due to inflammation can neutralize this suppressive effect, leading to the initiation of dysbiosis. Agar plate, dual-species and multi-species ecology experiments showed that H2O2 production by commensal bacteria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
51
2
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 47 publications
(58 citation statements)
references
References 34 publications
3
51
2
2
Order By: Relevance
“…Recently, it was shown that serum and blood components influence the microbiological balance by neutralizing the suppressive effect of commensal bacteria on pathogens, and thus might initiate a dysbiotic microbial biofilm composition (Herrero et al. ). Therefore, ensuring and restoring the health‐associated homeostasis of the resident oral microbiota as well as modulating the host immune response at diseased sites is a potential avenue for therapeutic intervention to promote oral health (Socransky & Haffajee , Marsh , ).…”
mentioning
confidence: 99%
“…Recently, it was shown that serum and blood components influence the microbiological balance by neutralizing the suppressive effect of commensal bacteria on pathogens, and thus might initiate a dysbiotic microbial biofilm composition (Herrero et al. ). Therefore, ensuring and restoring the health‐associated homeostasis of the resident oral microbiota as well as modulating the host immune response at diseased sites is a potential avenue for therapeutic intervention to promote oral health (Socransky & Haffajee , Marsh , ).…”
mentioning
confidence: 99%
“…In brief, 7 μL of an overnight culture of a commensal species was spotted onto an agar plate and incubated for 24 hours in aerobic conditions, as described by Herrero et al . Afterwards, 7 μL of the peroxidase solution was spotted next to spots of the commensal species and left to dry for 5 minutes at 37°C under aerobic conditions.…”
Section: Methodsmentioning
confidence: 99%
“…After 48 hours of anaerobic incubation, a calibrated photograph was taken of the agar plate. The magnitude of inhibition was measured from the edge of the commensal colony to the border of the inhibited pathogen colony using ImageJ (http://rsb.info.nih.gov/ij/download.html) (Figure ) …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations